PERANCANGAN ENSIKLOPEDIA AUGMENTED REALITY HIU DAN PARI YANG DILINDUNGI - Joy Christy, Joselly (Kartala, 2023)
The design of Interactive encyclopedia mobile app titled "Ensiklopedia Hiu dan Pari yang Dilindungi ", aspiring to be an interesting and informative media that can provide education to the public about Sharks and Rays regarding to their conservation status and protected species (12). contains Information on how to distinguish sharks and rays from their biological characteristics, area distribution, depth, which are presented through the encyclopedia as well as other information that supports the conservation of sharks and rays. The research method used in designing this encyclopedia application is a qualitative method with data collection techniques from books and the internet, observation, interview, and documentation with design thinking methode. Based on the results of research, author found that there is still a lack of public awareness regarding of the status of sharks and rays that are threatened with extinction, so that educational media and information about sharks and rays are needed. It is hoped that with this interactive mobile encyclopedia app able to become a medium to raise public awareness of the conservation status of sharks and rays.